2013
DOI: 10.14723/tmrsj.38.73
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Ag Nanostructures on Various Metallic Substrates

Abstract: Various kinds of Ag nanostructures were grown on various metallic substrates using hexakisphosphate (IP6) as a silver carrier agent. The Ag nanostructures with three-dimensional dendritic structure, the two-dimensional dendritic structure, the two-dimensional fractal structure, particles and nanowire structures were controllably obtained. The morphological control by IP6 using additional metallic materials is proposed. The structural properties of the Ag nanostructures were examined, and the growth evolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…3(c), the lattice fringes are constructed by so-called "1/3{422}" diffraction conditions, appeared by the elongation of {111} diffractions perpendicular to the nanosheet surface for the face centered cubic and diamond type crystals, and they are observable only for a sample that is atomically smooth and has very thin two dimensional flat sheets. 6), 21) It is also noted that the angle between two adjacent planes is not precisely 60 degrees, which is caused by the inclination of the Si(111) zoneaxis from the observation direction. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3(c), the lattice fringes are constructed by so-called "1/3{422}" diffraction conditions, appeared by the elongation of {111} diffractions perpendicular to the nanosheet surface for the face centered cubic and diamond type crystals, and they are observable only for a sample that is atomically smooth and has very thin two dimensional flat sheets. 6), 21) It is also noted that the angle between two adjacent planes is not precisely 60 degrees, which is caused by the inclination of the Si(111) zoneaxis from the observation direction. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…α-Fe 2 O 3 nanowires [6], CuO/Cu 2 O axial heterostructures [7], and ZrO 2 /SiO x core/shell nanowires [8] were synthesized by the thermal oxidation of metallic substrates in air at typically 673 -1173 K. Silver nanostructures were grown on various metallic substrates using a Ag-IP6 solution. A drop of the solution was dripped on metallic substrates, then kept for the treatment time of 10 s to several min at room temperature and dried [9].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the following structural control is one of examples, in which the shape control is caused by the carrier agent. Figure 5 shows SEM images of a variety of Ag nano-and micro-structures grown on various kinds of metallic substrates [9]. It was found that three-and two-dimensional dendritic Ag nanostructures were formed on (a) Cu and (b) CaSi 2 substrates, respectively.…”
Section: Fig 2 Tem Images Of (A) Mos 2 Powders and (B) H-mosi 2 Grown...mentioning
confidence: 99%
See 1 more Smart Citation